Pengaruh Laju Penambahan Doping Fosfor terhadap Struktur Kristal dan Luas Permukaan Spesifik Nanotitania dengan Metode Sol Gel - Vidi Nurhidayah; Posman Manurung; Ediman Ginting (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Research on the effect of the addition phosphorus doping using a syringe pump with the sol-gel method. The purpose of this study was to determine the effect of the addition rate of phosphorus doping to the crystal structure and specific surface area of TiO2. Doping increment rate used are 0,4; 0,2; 0,13 and 0,1 ml/hours of TiO2 samples were calcined at 450ºC for 5 hours. The powder was characterized by x-ray diffraction (XRD) and surface area analyzer (SAA) by the BET method. XRD diffractogram generally shows that the nanotitania crystal structure phase is anatase which is the result of TTIP synthesis as the main source of TiO2. Particle size analysis using XRD data on TiO2 with different rates in a row that is 10.13; 9.98; 9.25 and 10.33 nm. BET test results for each sample were 86.954; 87,367; 99,694; 96,295 and 96,187 m2/g. The results of XRD characterization can affect the surface area, getting smaller the particle size, the greater surface area will be obtained.